What makes people ready to conceive? Findings from the International Fertility Decision-Making Study. (August 2018) - Boivin, Jacky; Buntin, Laura; Kalebic, Natasha; Harrison, China
Abstract: This study investigated fertility decision-making in people currently trying to conceive, and examined whether factors that make people ready to conceive differ by gender and country. The study used data from the International Fertility Decision-Making Study, a cross-sectional study of 10, 045 participants (1690 men and 8355 women) from 79 countries. Respondents were aged 18–50 years (mean 31.8 years), partnered and had been trying to conceive for > 6 months (mean 2.8 years). Respondents indicated their need for parenthood; their own/partner's desire for a child; and the influence of certain preconditions, motivational forces and subjective norms in relation to readiness to conceive. Factor analysis of preconditions and motivational forces revealed four decisional factors: social status of parents, economic preconditions, personal and relational readiness, and physical health and child costs. Significant gender differences were found for desire for a child, decisional factors and subjective norms. Compared with men, women had higher personal desire for a child, and rated economic and personal and relational readiness as more influential. Men were more likely to rate subjective norms and social status of parents as more influential. Country comparisons found significant differences in personal desire for a child, partner's desire for a child, need for parenthood, preconditions, motivational forces and subjective norms. The results demonstrate that some decisional factors have a universal association with starting families (e.g. desire for a child), whilst the influence of others (e.g. personal and relational readiness) is dependent on contextual factors. These findings support the need for contemporary, prospective and international research on reproductive decision-making, and emphasize the need for effective fertility policies to take contextual factors into account.